An Analysis on the Denotative and Connotative Meaning of Lyrics of Creed’s Songs - Yulianus P Mangewa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2012)
Semantics as the study of meaning stands at the very center of the linguistic quest to understand the nature of language and human language abilities. It is obvious that semantics has an important role in understanding and comprehending a language, especially for English. Semantics not only concern with the study of meaning but also with the relationship between language and culture. Denotative meaning and connotative meaning: both of them are based on a relationship between words & world. Denotation is the meaning of a word which is primarily refers to the real word, the